Pharmaceutical Study of Acne Pacifying Herbo-mineral Cream- Mugdha Cream - Meena, Dr. Vandana (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: Acne is the disease which agitates the face during the primary phase of life, i.e. pubescent to adulthood. In Ayurvedic has been quoted as Mukhadushika or Yuvanpidika. At present, acne is anticipated to affect 9.4% of the global population, making it the eighth most prevalent disease globally. The cosmetics available are not suitable to all the condition; it may worsen the condition, as well as conventional treatment, is having its own precincts. The present study was undertaken, to validate the ancient Ayurvedic wisdom in light with the present day knowledge. Materials and Methods: Thus, in this study, after observing all Ayuvedic literature and many clinical reports, total six drugs, namely Shankha Bhasma, extract of Shalmali Kantak, Haridra, Manjistha, Nimba, and Rakta-chandan were selected to prepare oil-in-water (o/w) herb-mineral cream formulation with the suitable combination of the oil phase and aqueous phase along with preservatives. It was subjected to various physiochemical parameters such as type of emulsion, pH, spreadability, rheological studies, viscosity, and primary skin irritation. Results and Discussion: The result obtained was shown that viscosity of cream was in the range of 27001-27089 cps which indicates that the cream is easily spreadable by small amounts of shear. The rheological study showed pseudoplastic flow behavior of cream. Type of emulsion cream was o/w type. Primary skin irritation test showed the absence of redness, edema, inflammation, or irritation during irritancy studies. Conclusion: Thus, the Mugdha cream prepared is safe for use and could be a better remedy to cure acne.